2016
DOI: 10.1021/acs.joc.6b02452
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determination of (−)-SCH 64874 and Hirsutellomycin by Semisynthesis

Abstract: The structure of a C-symmetric epidithiodiketopiperazine alkaloid, SCH 64874, was determined by semisynthesis. The relative stereochemistry of the β-hydroxy carboxylic acid chain having three chiral centers was determined by comparison of the NMR data of the four possible diastereomeric β-hydroxy carboxylic acid fragments with those of SCH 64874. Condensation of the (-)-deacetylaranotin core with two enantiomeric β-hydroxy carboxylic acids revealed the relative stereochemistry of SCH 64874. The relative stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…During their investigation into the structural determination of (−)-SCH 64874, Tokuyama et al reported the synthesis and NMR characterization of the four possible diastereomers of the β-hydroxycarboxylic acid side chain [20]. Based on the obtained NMR data, the relative structure of the side chain of 1 was determined to adopt the (2′R*,3′R*,4′S*) configuration, as determined by the chemical shifts and the coupling constants between H-2′/H-3′ (J = 8.2 Hz) and H-3′/H-4′ (J = 3.2 Hz).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During their investigation into the structural determination of (−)-SCH 64874, Tokuyama et al reported the synthesis and NMR characterization of the four possible diastereomers of the β-hydroxycarboxylic acid side chain [20]. Based on the obtained NMR data, the relative structure of the side chain of 1 was determined to adopt the (2′R*,3′R*,4′S*) configuration, as determined by the chemical shifts and the coupling constants between H-2′/H-3′ (J = 8.2 Hz) and H-3′/H-4′ (J = 3.2 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…Azaphilones containing 6-membered rings constitute less than 10% of the hundreds of azaphilones isolated to date [ 5 ], and to the best of our knowledge, only eight compounds with a 2,4-dimethyl-3-hydroxyhexanoate moiety have been previously reported. More specifically, three thiodiketopiperazines, namely SCH 64874, 64875, and 64877, were isolated from the fermentation broth of an unidentified fungus [ 20 , 26 ], while three azaphilone-related polyketides, namely dothideomycetones A, B, and dothideomycetide A, were isolated from the CR17 fungal strain of the Dothideomycetes class (GeneBank accession number JQ867364) [ 27 ]. Furthermore, two sesquiterpenoids produced by Pithomyces chartarum (Dothideomycetes) were reported as intercellular adhesion molecule-1 (ICAM1) expression inhibitors in a patent literature [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…7 Danshen is a traditional Chinese drug used for the treatment of coronary artery disease and is known to possess antiviral, antioxidant, and antitumor activities. The reported total synthesis began with aldehyde 20, which was converted into bromide 21 via bromination and tosyl- In 1991, Castedo reported the synthesis of norsecosarcocapnine (29), which also gave access to secosarcocapnine (30) via an intramolecular Ullmann coupling (Scheme 5). 8 Subsequent Cope elimination of the piperidine motif gave Scheme 3 Ring-closing metathesis for the construction of the oxepin motif in janoxepin (19) by Taylor…”
Section: Oxepin Natural Productsmentioning
confidence: 99%
“…In 1991, Castedo reported the synthesis of norsecosarcocapnine (29), which also gave access to secosarcocapnine (30) via an intramolecular Ullmann coupling (Scheme 5). 8 Subsequent Cope elimination of the piperidine motif gave Scheme 3 Ring-closing metathesis for the construction of the oxepin motif in janoxepin (19) by Taylor…”
Section: Special Topic Synthesismentioning
confidence: 99%
See 1 more Smart Citation